Sodium Hypoclorid And Benzalkonium Chloride Usage As A Disinfectant In Residential Area Towards The Durability Of Non-Structure Building Materials - Lukas Kurniawan; Agung, SUMARNO (NAROTAMA UNIVERSITY, Indonesia, 2021)
It is seen that the world is experiencing health recession due to the coronavirus spread massively which resulting in a COVID-19 pandemic. To prevent and break the chain of coronavirus infecting in Indonesia, The Government and society are actively taking various efforts. One of them is doing a disinfecting process in residential areas. The impact of disinfectants on the structure of building materials is unknown and has never been tested in previous studies. This study aims to test empirically the effect of several chemicals from disinfectant ingredients towards the durability of non-structure building materials which are often used as residential materials. The sample of this study consisted of four group types, that is mortar, brick, hebel stone, and concrete brick. Each type of test object has a total of 6 variations of treatment by spraying or immersing H2O, BZK, and NaCIO chemicals and then testing the compressive strength after the age of the test object reaches 7, 14, and 28 days. The results of the study visually showed that the four types of specimens did not undergo physical changes during the duration of the test. The results of the research data also show that the four types of specimens experience anomalous results in compressive strength. The greatest compressive strength values ??for 4 types of specimens are not all at the age of 28 days, but at the age of 14 days, the largest compressive strength value for mortar is 30.74 MPa in the 6th variation of chemical immersion of NaCIO at 14 days, on hebel brick the largest compressive strength value is 2.41 MPa in the 3rd variation of spraying with chemical BZK aged 14 days, for red brick the largest compressive strength value is 11.48 MPa in the 4th variation of immersion with chemical BZK aged 14 days, and on the concrete brick the largest compressive strength value is 2.20 MPa in the 3rd variation of spraying with chemical BZK aged 14 days.